New research in financial markets - Biais, B.; Pagano, Marco (Oxford ; New York : Oxford University Press, 2001)
The selection of papers presented in these two volumes reflects the depth and breadth of the research interests of European scholars in financial economics. Topics discussed include asset pricing in the context of perfect markets and of market imperfections, the interaction between business cycle and financial imperfections, take over bids, and the interplay between banks and financial markets. These two volumes will provide an invaluable reference tool for scholars in the field.
Includes bibliographical references and index.
lje 11/07/16
Loan
Keywords: Financial markets; Stocks; Finance